1982
DOI: 10.1126/science.6800036
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Oropouche Virus from Man to Hamster by the Midge Culicoides paraensis

Abstract: Oropouche virus (arbovirus family Bunyaviridae, Simbu serological group) was experimentally transmitted from man to hamster by the bite of the midge Culicoides paraensis . Infection rates and transmission rates were determined after the midge had engorged on patients with viremia. The threshold titer necessary to enable infection or transmission by the midges was approximately 5.3 log 10 of the median lethal dose of the virus in suckling mice per milliliter of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
4

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 7 publications
1
32
0
4
Order By: Relevance
“…This species is typically found at high density during epidemics of ORO and bites humans both inside houses and outside (64,153). Biological transmission has been demonstrated via C. paraensis, from infected to susceptible hamsters and from infected humans to susceptible hamsters with transmission rates as high as 83% (146,147). Transmission of OROV between hamsters has also been demonstrated using the mosquito Culex quinquefasciatus, although this is much less efficient.…”
Section: Oropouche Virusmentioning
confidence: 98%
“…This species is typically found at high density during epidemics of ORO and bites humans both inside houses and outside (64,153). Biological transmission has been demonstrated via C. paraensis, from infected to susceptible hamsters and from infected humans to susceptible hamsters with transmission rates as high as 83% (146,147). Transmission of OROV between hamsters has also been demonstrated using the mosquito Culex quinquefasciatus, although this is much less efficient.…”
Section: Oropouche Virusmentioning
confidence: 98%
“…Symptoms last between 2 and 7 days, with some patients reporting a recurrence of these symptoms (3)(4)(5)(6)(7)(8)(9)(10). OROV is transmitted among humans via the biting midge Culicoides paraensis and is maintained in the wild by circulating in nonhuman primates, such as the pale-throated three-toed sloth (Bradypus tridactylus) and the black-tufted marmoset (Callithrix penicillata), though the vectors remain largely unknown (3)(4)(5)(10)(11)(12). Laboratory experiments and epidemiological surveys have reported that mosquitoes Aedes serratus, Aedes scapularis, Aedes albopictus, Culex fatigans, Culex quiquefaciatus, Coquilettidia venezuelensis, and Psorophora ferox are susceptible to OROV infection (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Arbo-bunyaviruses infecting humans and other animals are generally maintained in arthropod vectors and amplified in nonhuman vertebrates, although a few reports suggest that humans may serve as amplifying reservoirs during urban epidemics [1,9,[43][44][45][46]. Horizontal human-to-human transmission has rarely been reported and only occurs under specific circumstances, for example, exposure of healthcare personnel to CCHFVinfected patients [46].…”
Section: Virus Transmissionmentioning
confidence: 99%